Denture Induced Submandibular Hematoma in a Patient on Warfarin - Yeap, Boon Tat; Rajesh Kumar Muniandy; Hang, Lily Ng Mooi (2018)
A 79-year-old lady, who was taking warfarin, presented to the Emergency Department with a painless anterior neck swelling, which was associated with hoarseness of voice, odynophagia, and shortness of breath. She first noticed the swelling after she removed her dentures in the evening. On examination, she had an increased respiratory rate. There was a large submandibular swelling at the anterior side of her neck. Upon mouth opening, there was a hematoma at the base of her tongue, which extended to both sides of the tonsillar pillars. The patient was intubated with a video laryngoscope due to her worsening respiratory distress. Intravenous vitamin K and fresh frozen plasma were given immediately. the patient was admitted to the ICU for ventilation and observation. the hematoma subsided after 2 days and she was discharged well.